Immunisation Status Of Pregnant Women In Bihar - Yadav R. J; Singh Padam (Wolters Kluwer Medknow Publications, 1998)
Research Question: What is the coverage level of immunization and other maternal services by a modified technique developed by IRMS (ICMR) Delhi in comparison to standard WHO technique. Objectives: To study the â€"Coverage level for immunization, antenatal care and IFA tablets â€"Relationship of caste and education with the coverage levels. â€"Place and persons conducting deliveries. Study design: Cross-sectional. Setting: Both in rural and urban areas of Bihar. Participants: 375 mothers having children up to one year of age selected by a stratified random sampling technique developed by IRMS Delhi. Study variables: Immunisation status, antenatal care, Use of IFA tabs, Education of the female, Education of husband, place and person conducting the delivery. Statistical analysis: Proportions. Results: Overall immunization coverage was 42% for pregnant females. Coverage was high (60%) in urban areas compared to rural areas (40%). Coverage was low among females from SC/ST category, also when females and their husbands were illiterates. Similar trend was observed for antenatal care and IFA tabs. 90% deliveries took place at home and were mainly attended by village dais. Majority of mothers received immunization from some. Govt. agency lack of, awareness and lack of motivation were more commonly found as reasons for non-immunisation among SC/ST as compared to others. Lack of awareness was also found as a common reason for non-immunisation among illiterate females.